Enhancing Administrative Governance and Legal Information Management through the Legal Documentation and Information Network (JDIH) at Universitas Sebelas Maret - Mulyanto Mulyanto; Yugo Asmoro (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the implementation of the Legal Documentation and Information Network (JDIH) at Universitas Sebelas Maret (UNS) as a practical initiative to strengthen institutional legal governance within a Legal Entity State University (PTN BH). In the era of digital transformation and open government, the ability to manage and disseminate legal documents systematically is a vital component of good university governance. Using a qualitative-descriptive method with an empirical- administrative approach, this research observes how the UNS JDIH was developed, managed, and integrated within the university’s governance system. Data were obtained from document analysis, interviews with legal office staff, and direct observation during internal testing. Results show that UNS JDIH has reached Technology Readiness Level 5, indicating functional readiness for full implementation. The platform (jdih.uns.ac.id) consolidates all internal legal products such as Rector’s Regulations, Rector’s Decrees, and Circular Letters into a harmonized, web-based repository accessible to the public. JDIH UNS not only enhances transparency and accountability but also serves as an institutional mechanism for harmonizing legal policies in line with national regulations.